PERAN PENYULUH DAN KAPASITAS PETANI DALAM MEMBUDIDAYAKAN RUMPUT LAUT DI DESA LANGGERE KECAMATAN BONEGUNU KABUPATEN BUTON UTARA - Leli Sagita; Dasmin Sidu; Yoenita Jayadisastra (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2025)
The cultivation of seaweed in Langgere Village exhibits considerable promise; however, its potential has not been fully realized. This is primarily due to the limited capacity of farmers, the minimal role of fisheries extension workers, and the absence of sustainable facilities, infrastructure, and institutional support. The objective of this study is to ascertain the role of extension workers and the capacity of farmers in cultivating seaweed in Langgere Village, Bonegunu Sub-district, North Buton Regency. The population of this study was 206 seaweed farmers residing in Langgere Village. The sample size was determined using the Slovin formula with an error rate of 15%, resulting in a research sample of 36 seaweed farmer. The data were collected using a variety of research methods, including survey techniques, interviews, and documentation guided by a questionnaire. The research variables were divided into two categories: the role of extension workers and the capacity of seaweed farmers. The collected data is then subjected to descriptive analysis. The results indicated that the role of extension workers in Langgere Village is of significant importance in the development of seaweed cultivation. The role of educators and extension workers is to enhance farmers' technical knowledge. In their capacity as facilitators, extension workers play a pivotal role in assisting farmers in navigating the legal intricacies and acquiring the necessary capital for their business endeavors. In their capacity as organizers, extension workers play a pivotal role in facilitating the establishment of farmer groups and the subsequent management of production. As communicators, extension workers are responsible for data collection and routine monitoring of cultivation. Seaweed farmers have demonstrated effective managerial capacity by integrating their families into the business management process. From a technical standpoint, farmers implement suitable and efficient cultivation practices. Farmers demonstrate notable social capacity through their adherence to a culture of gotong royong, or mutual assistance, yet the formal cooperation with extension officers remains a developing area.